How much does the UK invest in intangible assets? Mauro Giorgio Marrano and Jonathan Haskel - Mauro Giorgio Marrano; Jonathan Haskel (Queen Mary University of London, Department of Economics, 2006)
We attempt to replicate for the UK the Corrado, Hulten and Sichel (2005, 2006) work on spending on intangible assets in the US. Their work suggests private sector expenditure (investment) on intangibles is about 13% (11%) of US GDP 1998-2000, with intangible investment about equal to tangible capital investment. Our work, using a similar method, suggests the UK private sector spent, in 2004, about \~A,Â127bn on intangibles, which is about 11% of UK GDP. The implied investment figure is around \~A,Â116bn (10% of GDP) which is about equal to UK investment in tangible assets. Of the \~A,Â127bn expenditure, (in round numbers) about 15% is spent on software, about 10% on scientific R&D, almost 20% on non-scientific R&D (design, product development etc.), about 14% on branding, about 20% on training and the rest on organisational capital.
Keywords: O47; E22; E01; 330; Intangible assets; R&D; Training; Organisational capital; Investment; Investition; Ausgaben; Privatwirtschaft; Immaterielles Anlageverm\~AƒÂgen; Vergleich; USA; Gro\~AƒÅbritannien